2018
DOI: 10.3390/polym10111248
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Applications of Molecularly Imprinted Polymers Modified TiO2 Nanomaterials: A Review

Abstract: Titanium dioxide (TiO2) nanomaterials have caused a widespread concern in the past several decades for their bulk characteristics and potential applications in many different areas. Lately, the combination between molecularly imprinted polymers (MIPs) and TiO2 nanomaterials have been proven to improve the relative adsorption capacity, selectivity and accelerate the rate of mass transfer of analyte which is not possible using TiO2 alone. Considering the unique performance of the MIPs modified TiO2 nanomaterials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(23 citation statements)
references
References 122 publications
0
23
0
Order By: Relevance
“…The modi ed TiO 2 lms by poly ethylene oxide (PEO), Polyvinyl achohol (PVA) polymers were evaluated on the level of crystallinity, optical transmission along with maximum major point on the photocatalytic action from thin-lms. Previous report indicated that polymer-modi ed lms showed seven times higher e ciency than the unmodi ed ones [8]. Theformation of carbonaceous polymeric deposit was observed on the titania surface due to Benzene activation.…”
Section: Introductionmentioning
confidence: 90%
“…The modi ed TiO 2 lms by poly ethylene oxide (PEO), Polyvinyl achohol (PVA) polymers were evaluated on the level of crystallinity, optical transmission along with maximum major point on the photocatalytic action from thin-lms. Previous report indicated that polymer-modi ed lms showed seven times higher e ciency than the unmodi ed ones [8]. Theformation of carbonaceous polymeric deposit was observed on the titania surface due to Benzene activation.…”
Section: Introductionmentioning
confidence: 90%
“…[53] The choice of the ZnO nano-support could have been an effort at avoiding the cross-selectivity, heterogeneous binding sites, and template leakage that characterizes MIPs on TiO 2 support. [65] The ZnO nanoparticles are better candidates as support for MIPs compared to the Al 2 O 3 nanoparticles, considering the insulating nature of Al 2 O 3 . [86] To a much lower extent compared to the CNTs, ZnO nanorods have also been used as support for MIPs.…”
Section: Zno Nano-supportmentioning
confidence: 99%
“…[ 64 ] The uniform binding site increases the rate of the recombination of the template molecule (analyte) with the MIPs, thus increasing the analyte's rate of reaction on the surface of the electrode. [ 65 ] Also, the MIPs on solid supports can be easily functionalized after the preparation of the MIPs. [ 66 ] It is also noteworthy that MIPs synthesis on solid support requires a smaller amount of template molecules compared to the homogeneous MIPs synthesis.…”
Section: Polymerization In Mips Based Sensors For Catecholamines Detectionmentioning
confidence: 99%
“…Molecular imprinting is considered as an engineering technique to synthesize receptors for a certain type of other molecules known as template molecules. This technique is fully described in several publications [1][2][3] which is based upon the formation of a three-dimensional polymer network around a template (analyte). After the template is removed, specific recognition sites are left as pores, which comply in shape, size and chemical functionality.…”
Section: Introductionmentioning
confidence: 99%